Preparation method and application of bisphenol phosphite melamine flame retardant
通过机械化学法合成的双酚亚磷酸酯三聚氰胺阻燃剂,解决了PBT材料阻燃性能不足和热加工时易挥发的问题,实现了高效、环保的阻燃效果,并简化了生产过程。
Patent Information
- Application Number
- CN202411484415.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-02-18
AI Technical Summary
现有聚对苯二甲酸丁二醇酯(PBT)材料的阻燃性能不足,且在热加工过程中易挥发,影响材料的力学性能和阻燃持久性。
采用机械化学法合成固态双酚亚磷酸酯三聚氰胺阻燃剂,通过亚磷酸、双酚物质和三聚氰胺的加成和酯化反应,制备出一种环境友好型的膨胀性阻燃剂。
The flame retardant has good thermal stability and is not easy to evaporate. It significantly improves the flame retardant performance in PBT materials, avoids the generation of toxic gases from traditional halogen flame retardants, and is simple in production, avoiding the "three wastes" problem.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemical industry, and in particular relates to a preparation method of bisphenol phosphite melamine and application thereof. Background Art
[0002] Polybutylene terephthalate (PBT) is a crystalline, linear saturated polyester and one of the five commonly used engineering plastics. It has excellent mechanical, electrical and molding processing properties. It is a thermoplastic engineering plastic with excellent comprehensive performance. It is widely used in the manufacturing industries of electronic appliances, automobiles, etc. to manufacture parts with high mechanical strength requirements, heat resistance, friction resistance, impact resistance and other applications. However, the limiting oxygen index of pure PBT is about 20%, and the flame retardant performance is poor (only UL94-HB grade can be reached). It is a flammable engineering plastic. When it burns, the melt is prone to continuous dripping, which spreads the fire source and causes fire accidents. Effective flame retardant modification of PBT can meet the requirements of flame retardant properties of polymer materials in various applications. In addition, in order to overcome the shortcomings of low notched impact strength and heat deformation temperature, PBT needs to be reinforced with glass fiber in most cases to adapt to its application in certain fields. PBT is an aromatic polyester containing benzene rings on the main chain, but it is usually difficult to form carbon after ignition, and it burns violently, and produces molten dripping to further spread the fire. Levehik and Weil summarized the thermal degradation mechanism of PBT in the literature "A review on thermal decomposition and combustion of thermoplastic polyesters. polymers for Advanced Technologies. 2004, 15: 691-700.", pointing out that the main reason for the flammability of PBT is the easy volatilization of aliphatic fragments when PBT is heated, and a considerable amount of tetrahydrofuran is produced during combustion. At the same time, they also proposed effective ways to flame retard PBT: 1. Change the degradation mode of PBT, add gas phase free capture agent to reduce the amount of combustible fragments produced during heating; 2. Improve the carbonization rate, add components that can promote carbonization, such as polyaromatic ring carbonizing agents, and phosphorus-based flame retardants can promote the decomposition of PBT and promote the formation of polyaromatic ring carbon layers.
[0003] Traditionally, PBT uses halogen flame retardants (usually halogen and antimony oxide synergistically) and adding 12%-20% can achieve better flame retardant effect (UL94V-0 level). However, halogen flame retardants will produce a large amount of toxic and corrosive gases when burned, causing a series of hazards to humans and the environment. In view of increasingly stringent environmental protection requirements, the application of traditional halogen flame retardants is greatly restricted and is gradually being replaced by halogen-free flame retardants.
[0004] Phosphorus-based flame retardants have become the mainstream of today's halogen-free flame retardant series. They are highly favored due to their low smoke and non-toxicity, and have become an important halogen-free flame retardant with broad application prospects.
[0005] Red phosphorus is a highly effective flame retardant for PBT. When red phosphorus is added to PBT and burned, it undergoes a series of chemical changes to form a layer of polyphosphoric acid film covering the polymer surface. It can catalyze the dehydration of PBT (oxygenated polyester) in the form of carbon cations, thereby playing a good flame retardant role. In practical applications, red phosphorus is still a hazardous chemical (explosion problems) and still requires microencapsulation technology for its surface treatment. The coloring properties of red phosphorus itself make it only suitable for red or black products.
[0006] Hypophosphites (represented by aluminum hypophosphites) and organic hypophosphites (represented by diethyl aluminum hypophosphites) are environmentally friendly phosphorus-based flame retardants that have received extensive attention and application in recent years. They have good flame retardant effects on PBT, especially when combined with nitrogen-based (melamine cyanurate, melamine polyphosphate, etc.) flame retardants to produce better synergistic flame retardant effects, enhancing the flame retardant effect of such flame retardants in PBT substrates. However, the industrial production methods of such flame retardants all use relatively expensive sodium hypophosphite as raw material, and a large amount of waste liquid is generated during the synthesis process and needs to be further treated, making the flame retardant cost of PBT relatively high.
[0007] Organic phosphate esters are common flame retardants of phosphorus-based flame retardants. Organic phosphate esters and nitrogen-based flame retardants (usually melamine and melamine cyanurate) are applied to PBT to produce good synergistic flame retardant effects. However, at the heat processing temperature of PBT, most phosphate esters are volatile and have poor heat resistance, which even affects the mechanical properties and flame retardant durability of PBT materials. The industrial synthesis of organic phosphate flame retardants requires phosphorus trichloride or phosphorus oxychloride as raw materials. The waste gas containing hydrogen chloride and waste liquid containing hydrochloric acid generated during the synthesis process need to be further treated. Since the hot processing (extrusion, injection molding) of thermoplastic PBT is usually around 240°C, considering the heat resistance of organic phosphate esters, the types of organic phosphate esters that can be subjected to multiple hot processing at this temperature are extremely limited.
[0008] In the literature "Flame Retardancy of Epoxy Resins Modified with Few-Layer Black Phosphorus Polymers (Basel). 2023Mar27;15(7):1655.doi:10.3390 / polym15071655.", diglycidyl ethers of bisphenol A-based epoxy resin (EP) modified with few-layer black phosphorus (BP) and red phosphorus (RP) were prepared using 4,4'-diaminodiphenyl sulfone as a curing agent. The thermal stability and flame retardant properties of the modified EPs were compared. It shows that red phosphorus and bisphenol A can improve the flame retardant properties of modified EPs. However, the coloring property of red phosphorus itself makes it only suitable for red or black products.
[0009] In the literature “Flame retardant epoxy resins from bisphenol-A epoxy cured with hyperbranched polyphosphate ester .Journal of Polymer Research Volume 18, pages 2229–2237, (2011)”, a new type of hyperbranched polyphosphate ester (HPE) was synthesized by the polycondensation reaction of bisphenol A and phosphoric acid trichloride. The formed HPE was characterized by FTIR, 1H NMR and 31P NMR to confirm its structure. Then, a series of flame retardant epoxy resins were prepared by curing bisphenol A epoxy resin with HPE and bisphenol A. The combustion behavior of the flame retardant epoxy resin was studied by limiting oxygen index (LOI) and cone calorimeter test, and its LOI value increased from 23 to 32. The industrial synthesis of organophosphate flame retardants requires phosphorus trichloride or phosphorus oxychloride as raw materials, and the waste gas containing hydrogen chloride and the waste liquid containing hydrochloric acid generated during the synthesis process need to be further treated.
[0010] In the paper “Fire Retardant Synergism Between Cyclic Diphosphonate Ester and Melamine in Poly (Butylene Terephthalate). Journal of Fire Sciences Volume 20, Issue 1 Pages: 71 – 83.”, the interaction between flame retardant additives and PBT was studied by thermal analysis and infrared spectroscopy. Cyclic diphosphonate and melamine provide excellent flame retardant properties in polybutylene terephthalate (PBT). An increase in oxygen index and an improvement in UL-94 classification to V-0 were observed. As a type of flame retardant, phosphonate has the characteristics of low toxicity and environmental friendliness compared to traditional halogen flame retardants, but the synthesis process is complicated and the cost is high. For example, in document CN103467520A, bicyclic phosphite is used to synthesize cyclic phosphonate in a two-step method under nitrogen conditions. The reaction steps are relatively large, the reaction time is more than 30 hours, and the reaction temperature is relatively high, which requires a lot of time and heat. Some domestic scholars also use ionic liquid to catalyze ethyl bicyclic phosphite and DMMP to synthesize cyclic phosphonate in a two-step method at 185 degrees, but the operation is cumbersome and the cost is too high.
[0011] In the paper “Fire retardant synergism between melamine and triphenylphosphate in poly(butylene terephthalate) Polymer Degradation and Stability Volume 91, Issue 9, September 2006, Pages 2093-2100.”, the flame retardant efficiency of melamine (MA) and triphenylphosphate (TPP) in polybutylene terephthalate (PBT) was investigated by limiting oxygen index (LOI) and UL94 tests. After adding 10 wt. % MA and 20 wt. % TPP, the LOI increased from 20.9 to 26.6 and reached the UL94 V-0 rating. SEM and DSC analysis showed that the flame retardants were compatible with PBT and promoted the crystallization of PBT. The occurrence of the interaction between MA + TPP and PBT was elucidated by TGA, dynamic FTIR, and pyrolysis / GC / MS. However, the volatilization temperature of the two substances in the flame retardant is lower than the thermal processing temperature (extrusion and injection molding temperature) of PBT. The volatilization of the two flame retardants is inevitable during the thermal processing of PBT, which is a defect of this component. Triphenyl phosphate (TPP) has partial volatilization and discoloration due to its poor temperature resistance, which affects the color and performance of the product. Free melamine will volatilize at this processing temperature and remain on the mold surface during injection molding and demolding, forming mold deposits. Summary of the invention
[0012] The purpose of the present invention is to provide a method for producing a PBT flame retardant. More specifically, the present invention provides a method for preparing a solid bisphenol phosphate melamine flame retardant synthesized by a mechanochemical method and its application. The synthesis method does not involve the problem of three wastes and belongs to an environmentally friendly clean production process. The flame retardant has good thermal stability.
[0013] The invention adopts phosphorous acid, bisphenol substance and melamine as raw materials to synthesize bisphenol phosphite melamine by solid-state mechanochemical method.
[0014] The bisphenol substances are bisphenol A (2,2-bis(p-phenylpropane)), bisphenol S (4,4-dihydroxydiphenyl sulfone) and mixtures thereof.
[0015] The preparation method of the bisphenol phosphite melamine flame retardant is completed in two steps. The first step is an addition reaction. First, phosphorous acid, bisphenol material and melamine are evenly mixed, put into a high-energy mill for grinding and crushing, and phosphorous acid and melamine undergo an addition reaction.
[0016] The second step is esterification reaction. The material of the first step is taken out from the high-energy mill, put into an oven for heating and esterification reaction to complete the reaction. The finished product is then cooled and crushed.
[0017] The first step of the addition reaction of melamine and phosphorous acid is completed in a high-energy mill, which is a vibration mill, a planetary mill or a stirring mill. The grinding time is 1 to 1.5 hours, and the obtained powder has a medium particle size (D50) of less than 12 microns; the following reaction occurs: In the second step, the reaction product obtained in the first step is subjected to an esterification reaction with a bisphenol substance:
[0018] The second step esterification reaction is between 220℃ and 240℃. After maintaining this temperature for 10 minutes, the negative pressure is maintained at 0.02MPa-0.05MPa and heating is continued for 60 minutes to 90 minutes. Generally speaking, the heating time takes the upper limit when the temperature is low, and the heating time takes the lower limit when the temperature is high.
[0019] The bisphenol substances referred to in the present invention are bisphenol A (2,2-bis(p-phenylpropane)), bisphenol S (4,4-dihydroxydiphenyl sulfone) and mixtures thereof.
[0020] The molar ratio of melamine to phosphorus in phosphorous acid is (1.4-1.8):1, and the molar ratio of bisphenol to phosphorous acid is 1:(1.8-2.3).
[0021] The present invention also provides a bisphenol phosphite melamine flame retardant, which is prepared by the preparation method described in the above scheme.
[0022] The present invention also provides the use of the bisphenol phosphite melamine flame retardant described in the above scheme in polyester PBT.
[0023] The mechanochemical preparation method of the PBT flame retardant bisphenol phosphite melamine of the present invention avoids the problem of "three wastes" that need to be treated in the production process, the raw materials are simple and easy to obtain, the production process is simple, and almost 100% product yield is obtained. The obtained finished product uses phosphorous acid as an acid source, bisphenol substances as a carbon source, and melamine as a gas source expansion flame retardant. This flame retardant belongs to a "trinity" single compound expansion flame retardant (carbon source, acid source, and gas source exist in the same molecular structure), and the flame retardant exhibits good thermal stability. Of course, if bisphenol S is used as a raw material, the flame retardant efficiency of phosphorus and sulfur as acid sources will be better. Under the condition of achieving the same PBT flame retardant grade, the added amount of the finished product obtained by using bisphenol S as a raw material is lower.
[0024] In the present invention, the reaction of melamine, phosphorous acid and bisphenol substances is an addition and esterification reaction, and the obtained product has good thermal stability. When added to PBT for thermal processing, bisphenol phosphite melamine is not easy to volatilize. Compared with other additive flame retardants, such as a mixture of melamine and triphenyl phosphate, when used as a flame retardant, it forms free melamine volatiles during thermal processing, forms mold deposits on the mold during injection molding, and affects the final quality of the plastic product. DETAILED DESCRIPTION
[0025] The protection content of the present invention is described in detail through the following specific implementation methods. The specific described embodiment is only an example within the scope defined in the claims and does not represent the scope of protection required by the claims.
[0026] Raw materials, equipment and testing methods used in the examples Raw materials used in the preparation of flame retardants Phosphorous acid: Phosphorous acid: Shijiazhuang Tiancheng Additive Factory, phosphorous acid (H3PO3) mass fraction ≥ 98% Melamine: Sichuan Jinxiang Sairui Chemical Co., Ltd. has a purity of more than 99.8% Bisphenol A: Shandong Luxi Chemical Co., Ltd. Purity greater than 99.5% Bisphenol S: Pingdingshan Runze Chemical Co., Ltd. Purity greater than 99% Raw materials required for flame retardant evaluation PBT: Changchun Synthetic Resin Factory Co., Ltd. Fiberglass: Jushi Group Co., Ltd. ECS14-4.5-588 Equipment used for flame retardant preparation The first step of the addition reaction is to crush and grind in a 5-liter vibration mill. The grinding medium is stainless steel balls. The materials are mixed manually in a plastic bag before grinding. The mixed materials are moved into the vibration mill for crushing and grinding. When the required grinding time is reached, the discharge valve is opened to discharge the materials.
[0027] The second step esterification reaction is carried out in a high temperature oven with temperature control, negative pressure extraction and time recording.
[0028] The finished product is crushed in a swing mill. The particle size can be adjusted according to the needs of the crushing time.
[0029] Equipment used for flame retardant evaluation Extruder: TSH-35B from Nanjing Tengdahe Machinery Equipment Co., Ltd. Injection molding machine: SA860 / 26G from Haitian Plastic Machinery Group Co., Ltd. UL94 horizontal and vertical combustion test machine: Guangzhou Automation Equipment Co., Ltd. GC-UL-A Testing equipment and evaluation methods involved in the experiment Powder particle size: LS-909 laser particle size analyzer is used, with water as the medium, methanol is dropped in, and the wet method is used to measure under the condition of suspension dispersant. The median particle size (D50) is its characteristic particle size.
[0030] PH value determination: accurately weigh 10.0g of the final product into a 200ml beaker, add 90ml of distilled water, stir continuously for 30min, and use PHSJ-4A laboratory PH meter produced by Shanghai Yidian Scientific Instrument Co., Ltd. to determine the pH value.
[0031] Water solubility analysis: Take 10.0 g of the final powdered product in the example, place it in a 200 ml beaker, add 90 g of distilled water, stir at room temperature for 30 minutes, filter with a pre-dried, constant-weight 4# sand core funnel, dry, weigh, and calculate the solubility.
[0032] Thermal stability determination: Take about 10 mg of the final product and place it in a crucible-type microcomputer differential thermal balance in an air environment, and raise the temperature from room temperature to 700 degrees Celsius by 10 degrees Celsius. Use the HTG-1 produced by Beijing Hengjiu Scientific Instrument Factory to determine the thermal stability of the product. The temperature at which the weight loss is 2% is used to determine the thermal stability of the product.
[0033] In the experiment, it was ensured that the particle size obtained after grinding the material in step (1) was less than 12 μm. Too large a particle size would affect the reaction and thus the quality of the final product; too small a particle size would require a long time to crush and increase energy consumption.
[0034] Evaluation of flame retardant performance: The flame retardant is mixed with PBT and glass fiber in a certain proportion, and the particles are drawn, cooled, crushed and dried in an extruder to obtain flame retardant PBT particles. Experimental specimens are made by injection molding machine, and 1.6 mm thick specimens are selected for UL-94 rating according to the vertical method in the "Standard for Determination of Combustion Performance of Plastics by Horizontal and Vertical Methods" (GB / T 2408-2008).
[0035] Table 1 First step reaction material ratio
[0036] In the second step, the material obtained in the first step is placed in a stainless steel square plate, and placed in a high-temperature oven with a preset temperature. After heating to the specified temperature and keeping it warm for 10 minutes, negative pressure is drawn to maintain the temperature for a certain period of time, and then taken out to cool. After crushing and screening with a swing mill, it is the finished product. Embodiment 1-10
[0037] Table 2 Different reaction conditions and finished flame retardant numbers
[0038] Table 3 Analysis results of finished products obtained in Examples 1-10
[0039] Flame retardant application in PBT flame retardant test and evaluation Test sample preparation A certain amount of PBT, glass fiber and the finished flame retardant prepared in the embodiment were weighed respectively, put into a mold bag and manually shaken to mix evenly, pulled, cooled and granulated in an extruder, dried in an oven and then injection molded in an injection molding machine, and a 1.6 mm sample was selected as a test piece.
[0040] Flame retardant performance test Place the test piece in the UL94 horizontal and vertical combustion tester, and take the average value of the three tests according to the vertical method as the measured value. Perform UL-94 rating according to the "Standard for the Determination of Horizontal and Vertical Methods for the Combustion Performance of Plastics" (GB / T2408-2008).
[0041] Table 4: Flame retardant PBT test piece material ratio and flame retardant rating results
[0042] It can be seen from the above flame retardant test that the flame retardant obtained by the scheme of the present invention has good flame retardant properties when added to PBT in an appropriate amount. The flame retardant obtained by using bisphenol S as a raw material has a lower addition amount and better flame retardant properties than the flame retardant obtained by using bisphenol A as a raw material.
Claims
1. A method for preparing a bisphenol phosphite melamine flame retardant, characterized in that: The product is a bisphenol phosphite melamine compound, which is obtained by solid-state synthesis using a mechanical alloying method; The specific steps include: In the first step of the addition reaction, phosphorous acid, bisphenol and melamine are uniformly mixed and ground in a high-energy mill, and phosphorous acid and melamine undergo an addition reaction. The high-energy mill includes a vibration mill, a planetary mill and a stirring mill. The grinding time is 1 to 1.5 hours, and the obtained powder has a medium diameter particle size (D50) of less than 12 microns. In the second step, the material from the first step is taken out from the high energy mill and placed in an oven for heating for esterification reaction. The esterification reaction temperature is between 220°C and 240°C. After maintaining this temperature for 10 minutes, the negative pressure is reduced to 0.02MPa-0.05MPa and heating is continued for 60 minutes to 90 minutes.
2. The method for preparing the bisphenol phosphite melamine flame retardant as claimed in claim 1, characterized in that: The bisphenol substances include bisphenol A, bisphenol S and mixtures thereof.
3. The bisphenol phosphite melamine flame retardant as claimed in claim 1 or 2, characterized in that: The raw material ratio used to prepare the flame retardant is as follows: The molar ratio of melamine to phosphorous acid is (1.4-1.8):1, and the molar ratio of bisphenol to phosphorous acid is 1:(1.8-2.3).
4. Use of the bisphenol phosphite melamine flame retardant according to claims 1-3 in PBT.
Citation Information
Patent Citations
Synthetic method for fire retardant cyclic phosphoric ester for padding dacron fabric
CN103467520A